Uma história de sucesso do comércio tradicional compartilhado com o comércio eletrônico:estudo de caso da Americanas.com - Silva, Jose Jorge de Freitas (2002)
This work is centred on studies about e-commerce as the comercial form in the companies. lt s main objective was the investigate this comercial practice which is based on this,describe which features are differents using e-commerce, exploring the conceptual, technical, and strategic characteristics for the creation of a suitable e-commerce structure, taking into consideration the logistics focus of the flow of goods and services commercialized on the Internet and the e-business to e-consumer relation. The research intends to focus on the logistic chalienges in which the current ways of commerce practice are, showed by the Brazilian Sites of this department store niche. To do so, themes and concepts of the technological innovation area as well as Marketing, lnternet E -commerce and lntegrated logistics were tackled. The purpose is to check what are the basic requirements to solve the problem of Iogistic and goods flow, goods and services commercialized for the finally consumer by a case study applied at the Americanas Site (www.americanas.com.br), which is a virtual electronic environment of business and commerce at the retailer department store of the Brazilian Group. Throughout studies related to the problem of logisties and the supply chain management, the appliance importance of the new recommendations of critical success factors, inserted into the mentioned model of business virtual environment, was testified.